2016
DOI: 10.3390/nu8070401
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Reduced Gluten Barley Diet with Oral Prolyl Endopeptidase Effectively Abrogates Enteropathy-Associated Changes in Gluten-Sensitive Macaques

Abstract: Celiac disease (CD) is an autoimmune disorder that affects approximately three million people in the United States. Furthermore, non-celiac gluten sensitivity (NCGS) affects an estimated additional 6% of the population, e.g., 20 million in the U.S. The only effective treatment of CD and NCGS requires complete removal of gluten sources from the diet. While required adherence to a gluten-free diet (GFD) is extremely difficult to accomplish, efforts to develop additional supportive treatments are needed. To facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…in the feed given to gluten-sensitive rhesus macaques (Sestak et al, 2015). Furthermore, symptoms due to prolamin consumption in these animals were not observed when this low-hordein barley feed was supplemented with a prolamin-degrading enzyme (Sestak et al, 2016). Future research using decreased-gluten wheat will be necessary to expand on these findings.…”
Section: Discussionmentioning
confidence: 92%
“…in the feed given to gluten-sensitive rhesus macaques (Sestak et al, 2015). Furthermore, symptoms due to prolamin consumption in these animals were not observed when this low-hordein barley feed was supplemented with a prolamin-degrading enzyme (Sestak et al, 2016). Future research using decreased-gluten wheat will be necessary to expand on these findings.…”
Section: Discussionmentioning
confidence: 92%
“…Tuberculin skin tests were negative for each individual. The 6 GS macaques had previously been reported with celiac-like GS, i.e., an equivalent of human CD [45]. Approximately 0.5 g of stool were obtained from at least 3 representative macaques at each time point when fed gluten-modified diets: conventional monkey chow, i.e., wheat gluten-containing diet (GD), gluten-free diet (GFD), conventional barley gluten-derived diet (BOMI) and reduced gluten barley-derived diet (RGB) (Supplementary Materials Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Proximal jejunum biopsy tissues from 4 GS and 6 healthy control macaques fed GD for at least one year (long-term GD) were collected and processed as described [45]. Half of the collected biopsies were preserved in 5 mL of RNA-later solution (Qiagen Inc., Valencia, CA, USA) while second half was embedded in paraffin and 7 μm sections were used for immunofluorescent staining, i.e., confocal microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that the lys3a barley mutant reduces prolamin-related symptoms when it replaces conventional barley in the feed given to gluten sensitive rhesus macaques [76]. Furthermore, symptoms due to prolamin consumption in these animals were not observed when this low hordein barley feed was supplemented with a prolamin-degrading enzyme [77]. Future research using reduced gluten wheat will be necessary to expand on these findings.…”
Section: Discussionmentioning
confidence: 79%